Organizational Performance: Motivation and Discipline - Raden Rijanto (Formosa Journal of Applied Sciences, 2023)
The development of an organization is inseparable from the existence of high motivation and discipline as well as well-established togetherness. This study aims to determine and analyze the performance of cooperatives in terms of motivation and discipline of members. Research findings, motivation and discipline have a positive effect on cooperative performance both individually and simultaneously. It is important for cooperative management or administrators to evaluate cooperative performance on a regular and scheduled basis to evaluate cooperative management. The causal factors are not explained in detail, this can be a consideration for further research. Digital aspects that are relevant to the cooperative management system can also be considered to see the performance of cooperatives in the digital era, in I4.0.